Democratic dialogues that make cities ‘work’ - Huybrechts, Liesbeth; Dreessen, Katrien; Schepers, Selina; Calderón Salazar, Pablo (My University, 2016)
The field of Strategic Design supports designers in researching and designing for the complexity of today’s cities by embracing the idea of strategic dialogue, in which designers align with different actors and their interests. In this article, we discuss how democratic dialogues – foregrounded in the Participatory Design (PD) tradition – play a role in complex urban design processes (i.e. ‘infrastructuring’) and entail different types of dialogues of which strategic dialogue is merely one. After framing Strategic Design and PD, we describe five designer roles and their associated dialogues. This description forms the basis of an exploratory typology of democratic dialogues that was applied and exemplified in a case study about a Living Lab in the neighbourhood of Genk. The Lab attempts to design alternative futures for work in the city together with citizens, public and private organisations. We claim that engaging with this typology allows designers to understand and design infrastructuring processes in the urban context and to open up different design dialogues and roles for discussion.
Keywords: 62 Ciencias de las Artes y las Letras::6201 Arquitectura; ODS 11 - Ciudades y comunidades sostenibles; democratic dialogues; living lab; urban context; designer roles; infrastructuring.